IMPLEMENTASI RESTORATIVE JUSTICE SEBAGAI DISKRESI DALAM KASUS PENGANIAYAAN RINGAN DI POLRES MOJOKERTO - Wijaya, Muhammad Aditya Kusuma; Handayati, Nur; Borman, M.Syahrul (Gapenas Publisher, 2025)
This study aims to analyze the implementation of restorative justice as a form of discretion in the settlement of minor abuse cases at the Mojokerto Police Station, as well as to identify the obstacles encountered in the process. The research method used is a sociological juridical approach with data collection techniques through literature studies and interviews with investigators at the Mojokerto Police Station. The results show that the Mojokerto Police have applied a restorative justice approach to minor assault cases by referring to Perpol No. 8 of 2021 and the provisions of Article 18 of Law No. 2 of 2002 on the Police. This discretion is exercised through penal mediation between the perpetrator and the victim, resulting in a peaceful agreement that leads to the termination of the investigation. However, this process is not without various obstacles, including a lack of public understanding, limited investigator resources, and cultural and administrative barriers. The conclusion of this study confirms that although discretion in the form of restorative justice has become an effective and humane legal solution, institutional strengthening, training of officials, and public education are still needed for its optimal implementation